Prevalence of lower urinary tract symptoms, urinary incontinence and retention in Parkinson's disease: A systematic review and meta-analysis - Li, Fang-Fei; Cui, Yu-Sha; Yan, Rui; Cao, Shuang-Shuang; Feng, Tao (Frontiers in Aging Neuroscience, 2022)
Background: Lower urinary tract symptoms (LUTS) are common non-motor symptoms but are often overlooked in Parkinson’s disease (PD). The prevalence of LUTS in PD is inconsistent among different studies. Objective: To estimate the prevalence of LUTS, urinary incontinence, and urinary retention in PD patients, then, investigate potential sources of inconsistency in prevalence estimation. Methods: We searched PubMed, EMBASE, and Web of Science databases from inception to May 2022. Studies reporting the prevalence of LUTS or LUTS subtypes in PD were included. Pooled prevalence of LUTS, LUTS subtypes, urinary incontinence, and urinary retention was calculated via random-effects models. Meta-regression and subgroup analyses were performed. Results: Of 7358 studies after duplicate removal, a total of 73 studies comprising 14937 PD patients were included. The pooled prevalence of LUTS was 61% (95% CI 53 to 69%; 27 studies; n = 5179), while the pooled prevalence of storage symptoms and voiding symptoms was 59% (44 to 73%; 9 studies; n = 798) and 24% (14 to 33%; 11 studies; n = 886), respectively. The pooled prevalence of urinary incontinence, retention and post-void residual (PVR) volume ≥100 ml were 30% (95% CI 22 to 39%; 21 studies; n = 6054), 27% (17 to 37%; 14 studies; n = 1991), and 4% (1 to 7%; 5 studies; n =439), respectively. The prevalence of LUTS, urinary incontinence, or urinary retention was significantly associated with diagnostic methods. Conclusion: LUTS and its subtypes present in a significant proportion of PD patients. It is necessary to use standardized and validated methods to detect and screen LUTS and its subtypes.